We're making a list and we're checking it twice, gonna find out what makes digital forensic examiners suffice - Morris, Sarah; Hadgkiss, Melissa; David, Anne; Guinness, John; Frewin, Charles (Wiley, 2023)
Digital forensic examinations have grown in breadth and depth at a currently unsustainable rate. Digital Investigations now feature in around 90% of criminal cases, demonstrating that digital evidence is crucial to forensic investigations. Due to the high number of cases, most law enforcement units have significant backlogs of devices waiting for analysis. As the field of Digital Investigation has grown, it is no longer solely related to criminal investigations, with the techniques also supporting civil, private, and corporate activities. Given the evident challenges, it is logical that more digital forensic experts are needed to keep pace with the field's complexities and demands. Identifying what characteristics and skills make a digital forensic expert enables an evaluation to ensure that any new staff are fit for purpose. There is a growth in academic, civil, corporate, and intelligence-based activity within the field. Each area defines their standards, field scope, and expertise level. Still, as any case has the potential to become a matter of criminal investigation, surely the focus needs to be on the standards required to ensure evidence is admissible for that purpose. As expertise levels can vary, it is also necessary to challenge the level at which an expert is defined and the implications of this decision. By identifying what makes an expert in this unique forensic science area, it is possible to explore the potential challenges the field faces in obtaining, retaining, and training staff.
Keywords: data recovery; digital forensic expert; Digital Forensics